Pendampingan Pemanfaatan Google Site Sebagai Media Pembelajaran Berbasis Web di SMPN 7 Semarang - Rakasiwi, Sindhu; Kurniawan, Defri; Hidayat, Erwin Yudi; Zeniarja, Junta; Dzaky, Azmi Abiyyu; Haresta, Alif Agsakli (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2025)
A website is the heart of an institution, school or company profile. With a web appearance that is always active and always has useful content, it will add to the image of the owner of the website. Because of this, the community service team wants to provide assistance to teachers so that they can also contribute to filling the website. So not only IT teachers can contribute to the website, but all teachers can contribute so that the website can be more active and interactive for students, parents of students and even for the general public who want to know information about SMPN 07 Semarang. And through this assistance, it also utilizes the Google site for more interactive learning and students are also more active in creating learning for the future.